Violências e seus efeitos no bairro do PAAR, Ananindeua/Pará - COSTA, Fernando Augusto Ribeiro (Universidade Federal do Pará, 2023)
We aimed, through the use of ethnographic procedures, to investigate, analyze and reflect on the effects of violence on how living and coexistence are established, organized and reproduced in the daily lives of individuals who live in the midst of it, especially in its subjective sense, especially in PAAR, a neighborhood on the outskirts of the Metropolitan Region of Belém, capital of the State of Pará. It is observed that in these relations there are elements of a coexistence based on mutual support and understanding, since the subjects have to live in the same side of coexistence and that, even for families whose members were considered suspects of illicit acts and barbarically exterminated, such attitudes do not disappear, but are reinforced. Conducting this reflection led us to seek to understand the nuances of a theme worked on under the most diverse aspects, which is always a task impregnated with the challenge of proposing a different look, an innovative analysis, or a conception so new that it can even respond to the longing to give ready-made answers to situations that are quite complex. Thus, numerous authors warn about the risk of aprioristic views and biases of thought that end up directing the analysis and, consequently, the conclusions. One such author is Slavoj Žižek. By working on the notions of subjective violence and objective violence, from a perspective of search and not of definitions, this author helps in the understanding of the multiplicity of visions and points of view while provoking the research to go in search of the confrontation of a reality full of symbolism in detriment of a Real full of Ideology.